Pengaruh Model Project Based Learning Terhadap Keaktifan Belajar dan Retensi Siswa - Fuan Maharani; Asrin Asrin; Arif Widodo (Journal of Classroom Action Research, 2023)
The research objective was to determine the effect of the Project Based Learning (PjBL) model on active learning, the effect of the PjBL model on student retention and the effect of the PjBL model on active learning and student retention simultaneously. This research is included in the type of experimental research in the form of a quasi-experimental posttest only control group design. Activeness research data was obtained by observation while retention data was obtained by conducting tests on students. The resulting data is in the form of population data with research samples focused on two schools, namely SDN 2 Gerung Utara and SDN 4 Gerung Utara. The sample is determined by probability sampling technique. The analysis in this research uses descriptive analysis which is used to describe data on student learning activeness and retention. In addition to descriptive analysis, this study also used inferential analysis using multivariate analysis of variance (MANOVA) to reveal the relationship between the variables studied in the study. The results of this study are that there is an effect of the PjBL model on active learning, there is an effect of the PjBL model on student retention, and there is an effect of the PjBL model on active learning and student retention simultaneously. The research results can be used as a reference for further researchers with similar research topics